A comparative Analysis of Symmetrical and Asymmetrical Cascaded Multilevel Inverter Having Reduced Number of Switches and DC Sources - Lipika Nanda; A Dasgupta; U.K. Rout (Institute of Advanced Engineering and Science, 2017)
As multilevel inverters are gaining increasing importance .New topologies are being proposed in order to achieve large number of levels in output voltage. A simplified MLI topology has been presented with both symmetrical and asymmetrical configurations. This paper represents a comprehensive analysis of above mentioned topology with FFT analysis,switching and conduction losses of the inverter.Hence efficiency at different carrier frequencies has been calculated successfully.Results are verified with simulation studies.Multilevel inverters are currently considered as a better industrial solution for high dynamic performance and power-quality demanding applications, covering a wide power range.